Active tunable THz metamaterial array implemented in CMOS technology. (15th December 2020) - Liu, Yongshan; Sun, Tong; Xu, Yong; Wu, Xiaojun; Bai, Zhongyang; Sun, Yun; Li, Helin; Zhang, Haoyi; Chen, Kanglong; Ruan, Cunjun; Sun, Yuzu; Hu, Yuanqi; et al.
Abstract: Terahertz (THz) modulators offer multifaceted capabilities for various practical applications such as THz imaging, wireless communications, sensing, etc. However, compared to the modulation devices used for other electromagnetic bands, the ubiquitous proliferation of THz applications is severely impeded by the tremendous lack of complementary metal-oxide-semiconductor (CMOS)-compatible technology. Here we demonstrated a CMOS-based active tunable THz metamaterial array (C-ATTMA) with split-ring resonators (SRRs). The THz metamaterial can be externally controlled with an electrically controlled dynamic. The C-ATTMA fabricated by the 180 nm CMOS technology featuring a resonant frequency of 0.30 THz was connected to the source and drain of a bottom metal-oxide-semiconductor field-effect transistor (MOSFET) through the vias. By delicately controlling the MOSFET gate voltage, the equivalent circuit response of the C-ATTMA was actively engineered, enabling tailoring THz resonance frequencies. Under a gate voltage of 1.8 V, we successfully realized a resonant frequency shift of ∼35 GHz and 3° phase shift. The equivalent circuit successfully explained the principle of the change. Inductor–capacitor (LC) resonance and electric dipole resonance of single-layer and double-layer SRRs have also been studied. The exhibited CMOS-compatible electrically regulated THz metamaterials provided a potential method for voltage regulation of THz, which may contribute to THz wireless communications, information encryption, THz compressed sensing and imaging, etc.